El control de constitucionalidad de las leyes, la acción de tutela y la revisión de tutela; como un triangulo protector de los derechos fundamentales en colombia. (2007)
Colombia has a large number of constitutionality controls aimed at protecting fundamental rights, nevertheless, within those controls there are three that currently have become the most guarantors of the rights and the principle of the supremacy of the constitution, these controls are: the control of constitutionality, the action of guardianship and the review of guardianship. precisely with the purpose of confirming the previous appraisal, i realize the present monograph of degree. in this one it is a question of providing theoretical justificative expositionsof which three mentioned controls are in the present stadium of the national life, the most effective juridical tools that they try for the protection of the fundamental rights of the colombian population.